The value of the function f(x) and the g(x) become f(g(3)) = -5.
According to the statement
we have given that the values of f (x) and g(x), And we have to evaluate f (g(3)).
So, For this purpose, we know that the
Here f (x) 4 –1 –6 1 3
And the value of the g(x) 1 4 3 –4 –6
So,
Extracting the numeric values of the functions from the table, it is found that f(g(3)) = -5
f(g(3)) is the value of f(x) when x = g(3).
g(3) is the value of g(x) when x = 3.
Looking at the table, when x = 3, g(x) = 5, thus g(3) = 5.
f(g(3)) = f(5), which is the value of f(x) when x = 5. Looking at the table, this value is -5, thus, f(g(3)) = -5.
So, The value of the function f(x) and the g(x) become f(g(3)) = -5.
Learn more about Function here
https://brainly.com/question/2328150
#SPJ1